Antibiotic Sensitivity Test to Bacteria in the Postoperative Treatment Room at Royal Prima Marelan Hospital - Yohanes Yohanes; Muhammad Arafat Muchtar; Stefani Tania (International Journal Labs, 2025)
Nosocomial infections in postoperative patients are a serious problem in hospitals because they can increase the rate of illness, death, and treatment costs. One of the important steps in controlling these infections is to conduct an Antibiotic Sensitivity Test to Bacteria in the Postoperative Treatment Room at Royal Prima Marelan Hospital to determine the effectiveness of drugs against bacteria causing infection. This study aims to identify the types of bacteria found in the postoperative intensive care room of Royal Prima Marelan Hospital and assess the level of sensitivity to several antibiotics. The study used an observational descriptive design with a cross-sectional approach. A total of 10 samples were taken from air, wall surfaces, floors, beds, and medical equipment. Bacterial identification was carried out through culture and Gram staining, followed by sensitivity tests using the Kirby-Bauer method against the antibiotics levofloxacin, amoxicillin, and tetracycline. The results showed that the most common bacteria found were Bacillus sp. (60%), followed by Staphylococcus sp. (30%), and Streptococcus sp. (10%). Sensitivity tests showed that levofloxacin had the highest sensitivity level at 90%, amoxicillin sensitivity was 70% with 30% resistance, while tetracycline showed a balanced result between sensitive and intermediate at 50%. Based on these results, levofloxacin is still the most effective antibiotic against bacteria in the postoperative room, while amoxicillin and tetracycline are less effective. These findings are expected to support the selection of appropriate antibiotics and help control bacterial resistance in hospitals.